2009
DOI: 10.1002/jemt.20736
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscopic study on the cephalic cuticular sensillae of different larval stages of Antheraea assamensis, an indigenous silkworm species of Northeast India

Abstract: Scanning electron microscopy revealed the presence of a number of cuticular sensillae on the head of different larval stages of the "Muga" silk moth, Antheraea assamensis. These include four types of sensilla trichodea, bead-like folded sensilla, two types of sensilla basiconica, and sensory pegs. The study seems to be the first attempt in describing the morphology and distribution pattern of the cephalic cuticular sensillae of different larval stages of the silk moth Antheraea assamensis, an indigenous specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Many researchers documented that sensilla chaetica were likely mechanoreceptors, which monitored food texture and coordinated the power output of the muscles and the positions of the labrum and the mandibles (Schneider ; Zacharuk ; Zacharuk and Shields ; Dey et al . , ; Goldsmith et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers documented that sensilla chaetica were likely mechanoreceptors, which monitored food texture and coordinated the power output of the muscles and the positions of the labrum and the mandibles (Schneider ; Zacharuk ; Zacharuk and Shields ; Dey et al . , ; Goldsmith et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The sensilla are present in small and constant numbers throughout larval life, which was highlighted in research on lepidopteran larvae (Dey et al . , ; Goldsmith et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Sensillae chaetica were reported as hair like and the longest sensillum found in the mala of maxillae and ligula of the 2 nd , 4 th larval instar and on the pre-pupal stages of S. granarius. Many researchers reported that sensillae chaetica were play an important role in monitoring food textile coordinated the power output of the muscles and the positions of the labium, labrum and the mandibles and may act as mechanoreceptors ( Zacharuk and shields 1991;Dey et al 2009Dey et al , 2011Goldsmith et al 2014). Xu et al, (2015) reported that sensillae chaetica play an important role in the movements of the maxillary and labial palps for larval Anoplophora glabripennis as well as detect the structure of the tunnel.…”
Section: Discussionmentioning
confidence: 99%